2006
DOI: 10.1103/physrevb.74.241301
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties ofCoGaAs(110)

Abstract: We observed three magnetic states of an ultrathin, atomically well-ordered Co film grown on a cleaved GaAs͑110͒ substrate. For a Co thickness less than 3.4 monolayers ͑ML͒, we find a ferromagnetically dead layer associated with the formation of interfacial Co 2 GaAs. For thicknesses greater than 4.1 ML, the Co film grows with a bcc structure that contains 6 at. % Ga. The films are ferromagnetic with an easy axis along the ͓110͔ direction. This magnetic state persists up to a thickness of 7 ML, at which point a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Co films up to 35 nm were grown on GaAsð1 1 0Þ [1] with a magnetization slightly lower than the bulk value. A recent study showed that Co forms an interfacial alloy at the GaAsð1 1 0Þ surface followed by bcc Co containing 6 at.% Ga [23]. Using Sb as a surfactant partly leads to a removal of lattice distortions and to an improvement of the magnetic properties [24].…”
Section: Introductionmentioning
confidence: 97%
“…Co films up to 35 nm were grown on GaAsð1 1 0Þ [1] with a magnetization slightly lower than the bulk value. A recent study showed that Co forms an interfacial alloy at the GaAsð1 1 0Þ surface followed by bcc Co containing 6 at.% Ga [23]. Using Sb as a surfactant partly leads to a removal of lattice distortions and to an improvement of the magnetic properties [24].…”
Section: Introductionmentioning
confidence: 97%
“…Although such studies have been carried out for several decades, on substrates as varied as Si, Ga, As, Pt, Pd and highly oriented pyrolytic graphite (HOPG) [4][5][6][7][8][9], most of these studies were confined to pure metal NPs. Recently, bimetallic NPs have become an interesting research field due to certain properties of nanoscale alloys, which may exist in a number of structures and phases that are different from those of the corresponding bulk metals [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] For example, in the Co/Ge(111) heterostructure, the critical thickness leading to the paramagnetic-ferromagnetic transition lies between 5 and 8Å. 24 Such a magnetic dead layer could result from various phenomena: interdiffusion and formation of an interfacial alloy that is generally not ferromagnetic, 21,22,25 interfacial roughness, 23 proximity of a nonmagnetic material, 26 and strain at the interface. 27 Here, the structural and magnetic analyses do not allow us to determine precisely the origin of the FDL.…”
Section: B Magnetic Propertiesmentioning
confidence: 99%